Communication Strategies of Individual with Down Syndrome - Anik Lailatul Muniroh; Rohmani Nur Indah (Budapest International Research and Critics University, 2021)
The issue on language and communication disorder of individuals with Down Syndrome becomes the focus of this study. It explores the disorder as a language phenomenon represented in movie. Where Hope Grows movie describes the character with Down Syndrome struggling in communicating with people in his workspace and independent livelihood. The result of this study shows that the utterances have dissimilarities with common people particularly in phonological terms such consonant clusters produced as a singleton, omitted word final consonant, target fricatives and affricates are produced as stops, and aspirated voiceless stops in initial position are de-aspirated. Moreover, there are also issues within the syntactical terms such simple infinitive clauses with equivalent subjects, infinitive clauses with different subjects, and quotes as full clauses. Further studies should cover more elaborative communication strategies of speakers with Down Syndrome in more impromptu and spontaneous speech contexts.